The UK higher education after brexit : the question of mobility and fees - Madni, Messaoud; Afkir, Mohamed (University of Ammar Theledji -Laghouat, 2022)
Several sectors in the UK were affected by Brexit, including Higher education that is often regarded as part of the market economy sector. Higher education was particularly affected because of its strong ties with students coming from the Continent. The present study aims to present an understanding of the extent to which Higher Education in the UK is affected by the transformations brought by the Brexit. It is to spot what challenges this sector will face and what measures the authorities will take to appease the risks of those challenges. This study follows a descriptive-analytical method based on chronology to collect and analyse factual data around the UK Higher Education sector from the moment the idea of Brexit crystalized well up to now. Data were collected out of reliable articles, blogs, reports, and websites, then they were analysed chronologically to trace the changes occurring in the higher education sector. The findings of this work showed that the real changes in the UK’s higher education started to take place after the exit referendum of 23/06/2016. These findings can be analysed as follows: After having left the EU and having lost many EU higher education projects and opportunities, the UK tended to adopt new policies and schemes to compensate for the losses. This chiefly include the Turing scheme as well as the transnational higher education